UV-LEDs combined with persulfate salts as a method to inactivate microalgae in ballast water. (February 2023) - Rivas-Zaballos, Ignacio; Romero-Martínez, Leonardo; Moreno-Garrido, Ignacio; Moreno-Andrés, Javier; Acevedo-Merino, Asunción; Nebot, Enrique
Abstract: The Ballast Water Management Convention (BWMC) establishes limits for viable organisms in discharged ballast water. UV-based ballast water management systems (BMWS) are among the most common, especially those with low pressure (LP) and medium pressure (MP) mercury lamps. An interesting alternative to mercury lamps could be UV LEDs that have been developing over recent years. UVA, UVB, and UVC LEDs have been tested as a method to inactivate microalgae in ballast water. For this study, the diatom Phaeodactylum tricornutum was selected as a target organism. Comparing the D 2 (dose required to achieve two log reductions) for P. tricornutum from different UV treatments, it was observed that UVC LEDs were 74.2 % more efficient than UVB LEDs and, compared with previous studies, 48.1 % more efficient than UVC LP mercury lamps. If a five day dark post-treatment was combined with the UV irradiation to avoid photoreactivation, UVC LEDs were 90 % more efficient than UVB LEDs and, compared with previous studies, 36.8 % more efficient than UVC LP mercury lamps. No damage with or without photoreactivation was caused by UVA irradiation with doses up to 4·10 4 mJ cm −2 . The combination of peroxymonosulfate (PMS) with UVA, UVB and UVC LEDs did not significantly increase the inactivation, and the combination of the peroxydisulfate (PDS) with UVC LEDs slightly decreases the inactivation compared with UVC irradiation alone. In conclusion, UVC LEDs were the most efficient for inactivating P. tricornutum, and the combination of PMS and PDS with UV LEDs did not notably improve it. Graphical abstract: Unlabelled Image Highlights: UVA, UVB and UVC LEDs were tested on the microalgae Phaeodactylum tricornutum . The inactivation efficiency and the level of photoreactivation followed UVA<UVB<UVC. P. tricornutum was more resistant than viruses and bacteria at UVA, UVB and UVC. UVC LEDs are more efficient for microalgae inactivation than UVC mercury lamps. The combination of persulfate salts with UV LEDs did not increase the inactivation.